Phylogeography and genetic diversity of the Serrated Hinge-back Tortoise Kinixys erosa (Schweigger): implications for taxonomy and conservation - Ihlow, Flora; Gvoždík, Václav; Nagy, Zoltán Tamás; Kehlmaier, Christian; Chifundera, Zacharie Kusamba; Fritz, Uwe (Zootaxa, 2025)
The Serrated Hinge-back Tortoise Kinixys erosa inhabits moist forests across Central and West Africa and is known to show phylogeographic structure. Based on extended geographic sampling, we re-examined its phylogeography using three mitochondrial genes and up to 17 nuclear loci. The observed mtDNA variation was considerable and corresponds to two major and well-supported clades from the western and the eastern part of the distribution range. Within the western clade, samples from Ghana represent a well-supported subclade. Nuclear loci support the genetic distinctness of these groups showing the Ghanian population as the most divergent. This suggests that K. erosa comprises hitherto unrecognized distinct taxa. Since no sufficient morphological data are available, and it is unclear to which clade the name K. erosa (Schweigger) refers, we abstain from taxonomic conclusions, but identify the genetic clusters as distinct Management Units for conservation.